Application of the greedy algorithm to maximize advantages of cutting steel bars in the factory construction - Muzayanah, Rini; Tama, Endi Adika (Journal of Student Research Exploration, 2023)
Indonesia is one of the countries that is currently exuberant with development issues in order to balance the ongoing process of global modernization. In the infrastructure development process, the developer will enter into a contract with the contractor. This study aims to analyze the performance of the greedy algorithm in optimizing steel cutting with maximum profit to construction companies. The methods used include literature studies, program design, and program trials where the algorithm used is a greedy one. From the results obtained, it is evident that the Greedy algorithm can provide optimal steel cutting solutions because it works by calculating and deviating from all available separation settings, so there is no need to recalculate if the program performs that step.